Microsoft Access 2010 : 24-hour trainer - Griffith, Geoffrey L.; Bradly, Truitt L. (Indianapolis, IN : Wiley Pub., 2011)
Presents lessons and step-by-step instructions on how to create database applications using Microsoft Access 2010.
'Wrox programmer to programmer'--Cover.
Book is accompanied by one DVD-ROM bearing the same call number and availble at Makmal Digital, Perpustakaan Dr. Abdul Latiff.
Keywords: Database management; Database management